Gender and nutritional status based on weight-for-age (W/A) in toddlers and its association with stunting cases - Setiawati, Iin; Daniati, Dana (International Journal of Health Science and Technology, 2025)
Malnutrition remains a persistent public health issue in Indonesia, with the government yet to fully address the problem. In 2021, the prevalence of stunting in Indonesia decreased from 24.4% to 21.6% in 2022, with a national target of reducing it to 14% by 2024. In Trageh Public Health Center, the prevalence of stunting was recorded at 6.52% in 2023, while cases of wasting and underweight were 3.13% and 3.16%, respectively. This study aims to analyze the correlation between gender and nutritional status in toddlers with stunting. The research employed a correlational analytic design with a cross-sectional approach. The study population consisted of all toddlers (n = 243), with a sample size of 151 determined through simple random sampling. Univariate data analysis utilized frequency distribution tables, while bivariate analysis was conducted using Linear Regression with a significance level of α = 0.05. The findings revealed that nearly half of the respondents (n = 65; 43.05%) were female and classified as normal (non-stunted). Additionally, the majority of toddlers had good nutritional status and were not stunted (n = 93; 61.59%). Statistical analysis using Spearman's correlation test yielded ρ = 0.651, indicating no significant relationship between gender and stunting, whereas the correlation between nutritional status and stunting was statistically significant (ρ = 0.000).